2006
DOI: 10.1002/kpm.254
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge exploitation, knowledge exploration, and competency trap

Abstract: It is no surprise that knowledge exploitation and knowledge exploration have become the consistent theme in organizational learning literature. Strategy and organization theorists have similarly observed the dynamic capabilities anchored in a firm's ability to simultaneously exploit current technologies and resources to secure efficiency benefits, and creating variation through exploratory innovation. While some studies argue that excessive exploration or excessive exploitation can lead to a competency trap, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 107 publications
1
57
1
Order By: Relevance
“…Previous research has shown that organizational learning capabilities, including the exploration and exploitation of knowledge is the main source of competitive advantage (Kogut and Zander, 1992;Prahalad and Hamel, 1990;Liu, 2006). The study also mentions that an appropriately manage of balancing between exploration and exploitation becomes a major factor that can support the survival and prosperity of organization (March, 1991;Cohen and Levinthal, 1990;Levinthal and March, 1993).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous research has shown that organizational learning capabilities, including the exploration and exploitation of knowledge is the main source of competitive advantage (Kogut and Zander, 1992;Prahalad and Hamel, 1990;Liu, 2006). The study also mentions that an appropriately manage of balancing between exploration and exploitation becomes a major factor that can support the survival and prosperity of organization (March, 1991;Cohen and Levinthal, 1990;Levinthal and March, 1993).…”
Section: Introductionmentioning
confidence: 71%
“…In line with the opinion of March (1991), Sitkin et al (1994) defines exploitation of knowledge as learning activities that include the use of resources already owned by the organization, as well as the exploration of knowledge as learning activities that lead to the addition of new resources. Both definition of March (1991) and Sitkin (1994) indicates that there are two basic modes for the production of knowledge in organizations, namely the exploitation or exploration of knowledge (Liu, 2006). The process of knowledge exploitation is basically the process of acquiring competence by adopting, integrating and applying existing knowledge.…”
Section: Faculty Of Economics Universitas Islam Indonesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Common sources of preconceptions in industrial psychology include competency traps, success traps, path dependencies, and lock-ins. Competency traps involve organisations focusing on competencies they are already expert in, even when new technologies make that expertise increasingly irrelevant [20]. Success traps involve a period of successful organizational performance leading to stale ideas about what makes success for all time into the future [21].…”
Section: Industrial Psychologymentioning
confidence: 99%
“…Exploitation is basically the process of gaining competence by adopting, synthesizing, and applying current existing knowledge [27] [28]. Knowledge exploitation can be divided into internal and external knowledge exploitation.…”
Section: Knowledge Exploitationmentioning
confidence: 99%